Clinical polymorphism of acute disseminated encephalomyelitis: diagnosis, treatment, long-term prognosis. Lecture with the description of clinical cases - V. E. Avdeeva; A. S. Kotov (Русский журнал детской неврологии, 2023)
Acute disseminated encephalomyelitis is an acute autoimmune demyelinating disease that manifests as a widespread polyfocal asymmetric lesions of the central nervous system and, in some cases, optic nerves with the formation of corresponding neurological symptoms. This lecture presents basic information about acute disseminated encephalomyelitis with consideration of 5 clinical cases demonstrating the variety of manifestations of this disease in the practice of a neurologist.